Enucleation of solid pseudopapillary tumor with a preoperative nasopancreatic drainage stent in a child. Issue 4 (21st June 2017) - Tanaka, Keiichiro; Misawa, Takeyuki; Haruki, Koichiro; Saito, Ryota; Gocho, Takeshi; Akiba, Tadashi
Abstract: Solid pseudopapillary tumor (SPT) is a rare pancreatic tumor with low‐grade malignancy in children. A complete surgical resection can achieve a favorable prognosis. Although several reports have indicated that enucleation is considered a safe and effective treatment, the most significant complication is injury to the main pancreatic duct. The usefulness and safety of tumor enucleation after preoperative placement of an endoscopic nasopancreatic drainage stent (NPDS) has recently been reported. We present the case of SPT in a 10‐year‐old girl. To avoid and detect injury to the main pancreatic duct during operation, an NPDS was endoscopically placed before laparotomy. The patient underwent a complete enucleation of the tumor with the guidance of an NPDS. Our case is the first report of a successful enucleation of an SPT with a preoperative placement of an NPDS. This procedure may lead to safe enucleation of a pancreatic tumor with low malignancy, such as SPT, in children.